HUBUNGAN PENGETAHUAN, DUKUNGAN KELUARGA DAN DUKUNGAN PETUGAS KESEHATAN TERHADAP KEPATUHAN MINUM OBAT PADA PENDERITA HIPERTENSI - Topan, Topan; Berti Anggraini, Rima; Faizal, Faizal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Adherence to treatment is a crucial factor in the management of hypertension to prevent serious, potentially fatal complications. High community compliance with Puskesmas services has a positive impact not only on the reputation of the Puskesmas but also on the effectiveness of handling hypertension cases that do not comply with the treatment program. This research aims to analyze the relationship between the level of knowledge, family support, and support from health workers and adherence to taking medication in hypertension sufferers at the Rias Health Center, South Bangka Regency, in 2024.This research uses a cross sectional study design. This research was carried out by distributing questionnaires to 97 respondents who were in the Rias Health Center UPT work area on October 6 – November 2. The data collected was then analyzed univariately and bivariately using the chi-square test. The results of this study prove that there is a relationship between knowledge factors (p value = 0.000), family support with a value (p value 0.000) and support from health workers (p value 0.001) on compliance with taking medication in the work area of the Rias Health Center UPT South Bangka Regency in 2024. It is recommended that health institutions improve patient education programs on an ongoing basis and strengthen interactions between health workers and patients to increase compliance. Further research is recommended to explore other factors that may influence adherence, such as intrinsic motivation and patient psychosocial conditions.Keywords : Family Support, Health Worker Support, Hypertension, Medication Compliance, Knowledge